Globalization and Income Inequality : A European Perspective - Harjes, Thomas (IMF Working Papers; Working Paper, 2007)
There is growing concern in Europe over the impact of globalization on high and evenly shared living standards. These concerns have often surfaced in response to falling labor income shares in aggregate national income data. However, these data may tell little about the underlying distribution of incomes based on household disposable incomes. While summary measures of income distributions also suggest that inequality has increased in most industrialized countries, this development was very uneven and much less pronounced in euro-area countries, suggesting that broad phenomena such as trade liberalization and technological change may not be major drivers of inequality.